Determining the Force Required to Remove a Screw from a Human Vertebra - Balcar, Patrik; Vachata, Petr; Svoboda, Martin; Lodin, Jan; Lattner, Michal; Svoboda, Antonín; Pichlová, Edita (Manufacturing Technology Journal, 2025)
The article describes a pilot experiment of mechanical testing of 3D printed vertebrae with an inserted screw. The main goal of this work was to verify the design of a measurement methodology for experimentally determining the mechanical properties of vertebrae produced using 3D printing and also for determining the load-bearing capacity of a screw when it is drilled into a vertebra. The work describes the construction of a special fixture with which it is possible to clamp test samples for tensile testing. The stud screws were pulled out of a real or printed vertebra using a tearing machine. Testing was performed on porcine and 3D printed vertebrae. CT images of porcine spines obtained by a computed tomography scanner were used to create the printed vertebrae. This work verified the mechanical properties of printed and real vertebrae. In connection with this work, suitable printed materials and the necessary parameters of 3D printed samples will be sought so that they correspond to the necessary mechanical properties and can replace human vertebrae. It will then be possible to conduct laboratory investigations to obtain better results in spinal stabilization. The experiments verified the measurement methodology, compared the measured values between real and printed vertebrae, and also determined the next direction of research.
Keywords: Vertebra; Tensile test; Screw; Mechanical properties; 3D printing; Spinal stabilization